Avrupa Birliği ve Türkiye’de Bölgesel Kalkınma Bağlamında Devlet Yardımları - Sibel İnce Arıkan; Abuzer Pınar (Ankara Avrupa Çalışmaları Dergisi)
State-aids aiming at fostering industrialization and supporting regionaldevelopment are being allowed in the European Union (EU) provided that they arecompatible with the regulations. Despite that the aid discriminating betweenentrepreneurs and affecting the foreign trade is not being allowed in principle, thereare substantial aids, based on some certain principals, to some enterprises, particularlythe ones in relatively backward regions. Similar regulations such as "Priority Regionsfor Development" have been designed also in Turkey, as a country expecting a date forthe EU membership in the near future. However those regulations have been alteredquite often not necessarily for the primary aim, but particularly for the political rentexpectations. Thus there have been some deviations in regulations, and failure inpractice particularly in term of reducing regional income gaps. Despite that it is not aprecondition for the adjustment procedure of Turkey to the EU, the revision of theregional development policy to set certain principals for state-aids will both ease to getthe expected benefit and will also be helpful in adjusting to the fiscal rules of the Unionin a possible membership period.